The steel remains - Morgan, Richard K., 1965-; Orion Books (London : Orion Publishing, 2008)
Ringil "Gil" Eskiath, an effete mercenary who has been alienated from his aristocratic family, agrees to find and free his cousin who was sold into slavery, but while he tracks the young woman with two old friends--Edgar of the Majak tribe and the half-Kiriath Archeth--Gil hears rumors of more sinister things afoot.
Booklist, December 2008.
Library Journal, December 2008.
Adult
Keywords: Good and evil -- Fiction; Heroes -- Fiction; Magic -- Fiction; Wizards -- Fiction; Heroes and heroines -- Fiction; Fantastic fiction